2006
DOI: 10.1111/j.1582-4934.2006.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic reprogramming of poorly aggressive melanoma cells by a metastatic microenvironment

Abstract: Cancer pathogenesis involves dynamic interactions within the tumor-host microenvironment. Most noteworthy is cutaneous melanoma which is considered one of the few remaining cancers escalating in incidence [1,2], and thus represents a growing public health burden worldwide [3; for review, see 4; 5]. In addition, uveal melanoma is considered the most common primary intraocular cancer in adults [6], where metastasis occurs in an unpredictable manner in approximately 50% of patients with a primary tumor originatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 102 publications
(92 reference statements)
1
29
1
1
Order By: Relevance
“…Microenvironment is a key factor in tumor progression. Seftor et al 5 demonstrated that poorly aggressive melanoma cells acquired a vasculogenic phenotype when they were exposed to a microenvironment preconditioned by aggressive metastatic melanoma cells. The opposite effect has also been studied long ago by Illmensee et al 8 who showed that teratocarcinoma cells could be normalized by the blastocyst environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microenvironment is a key factor in tumor progression. Seftor et al 5 demonstrated that poorly aggressive melanoma cells acquired a vasculogenic phenotype when they were exposed to a microenvironment preconditioned by aggressive metastatic melanoma cells. The opposite effect has also been studied long ago by Illmensee et al 8 who showed that teratocarcinoma cells could be normalized by the blastocyst environment.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the case of osteosarcoma, for instance, although several cell lines have been established and characterized, few reliable animal models mimic all the aspects of human cancer, making it difficult to test valuable therapeutic strategies. 3 Since tumor microenvironment plays a key role in cancer development, [4][5][6] we investigated whether the dermis of a different anatomical site of mice would offer different characteristics than those of the flank. Thus, we chose the dorsal region of the foot and compared it to the flank in terms of cellular influx and reactivity upon antigen injection.…”
Section: Introductionmentioning
confidence: 99%
“…After tumor cells escape the primary site, the epigenome is subjected to microenvironmental signal modulation, conferring cellular plasticity and adaptability to new and inhospitable conditions (Seftor et al 2006;Hendrix et al 2007;Tam and Weinberg 2013). Indeed, multiple studies have unveiled evidence of specific epigenetic pathways involved in the metastatic progression of different cancer types (Cunha et al 2014;Gu et al 2015;Okada et al 2015;Tang et al 2015).…”
Section: G464vmentioning
confidence: 99%
“…Poorly aggressive melanoma cells acquired a vasculogenic phenotype when they were exposed to a microenvironment preconditioned by aggressive metastatic melanoma cells (Seftor et al, 2006). The opposite effect has also been studied long ago by Illmensee & Mintz (1976) who showed that teratocarcinoma cells could be normalized by the blastocyst environment.…”
Section: The Role Of the Microenvironment In The Development Of Cutanmentioning
confidence: 85%